Pengaruh Pemberian Dosis Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Kangkung (Ipomea reptans P.) - Eis Miftahul Mufidah; Antar Sofyan; Akhmad Gazali (Universitas Lambung Mangkurat, 2022)
Kangkung land (Ipomea reptans P.) is a vegetable that is much favored by the community, the demand for land spinach in Indonesia reaches 308,477 tons ha-1. The availability of kale plants must be sustainable to meet high market demand. One of the efforts that can be done is to increase the productivity of kale plants in suitable soil and environmental conditions. One way to increase the productivity of kale is by applying good technology for cultivation, including the use of fertilizers. Compound fertilizers are more practical to use because they already contain macro-nutrients in the form of nitrogen (N), phosphorus (P), and potassium (K). The study aimed to determine the effect of giving several doses of inorganic NPK fertilizer on the growth and yield of land kangkung. The study was carried out in the field of Jone village, Paser Regency, East Kalimantan from July to August 2020. This study used a single factor RAK, namely the administration of a dose of NPK fertilizer. There were 5 treatments and 4 replications, so there were 20 experimental units. Observation parameters consisted of leaf width, plant height, plant wet weight and number of leaves. The best dose of inorganic NPK fertilizer is 25 grams/plot or 250 kg/ha. Copyright ã 2022 Agroekotek View